Preparation method of coal liquefaction pitch-based foam carbon
By hydrolyzing the template agent and alkali liquid, partial separator is removed, impregnation capacity is improved, and carbonization is activated in contact with coal-liquefied asphalt, the problems of complex preparation process of coal-based foam carbon in the prior art are solved, and coal-liquefied asphalt-based foam carbon materials with high specific surface area and high strength are obtained.
Patent Information
- Application Number
- CN202411813266.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, the preparation process of coal-based foam carbon is complex, with a small specific surface area and low porosity. The high polyester foam used in the soft template method has a closed-cell membrane, which affects the microstructure and porosity of the material.
Coal liquefied asphalt is used as raw material, and the template agent is hydrolyzed by contacting the alkali liquid phase to remove part of the membrane, thereby improving the impregnation ability of the template agent. Then the pretreatment template was contacted with the asphalt slurry and carbonized activation treatment was carried out to obtain coal-liquefied asphalt-based foam carbon.
The pore size uniformity, porosity and carbon yield of foam carbon are improved. The obtained materials have a high specific surface area and high strength, which are suitable for industrial production and have a wide range of application scenarios.
Smart Images

Figure CN119591104A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of foam carbon preparation, and in particular relates to a method for preparing coal liquefaction pitch-based foam carbon. Background Art
[0002] Carbon foam is a lightweight porous carbon material with a three-dimensional network structure composed of pores and interconnected pore walls. It has the advantages of high strength, high conductivity, high temperature resistance, corrosion resistance, and low density. Carbon foam has good thermal conductivity, electrochemical properties, and wave absorption properties, and is a potential new market material. Coal liquefaction pitch is an asphalt-like substance obtained by solvent extraction and separation of direct coal liquefaction residues. It is mainly composed of polycyclic aromatic compounds and has the characteristics of easy polymerization or cross-linking, high condensation degree, high carbon yield, and low sulfur content. It is a high-quality precursor for the preparation of high-quality carbon materials.
[0003] At present, the main raw materials for preparing foamed carbon include organic polymers, mesophase asphalt, petroleum asphalt, naphthalene asphalt, coal and coal-based materials, biomass, etc. Using coal liquefaction asphalt as the carbon source to prepare foamed carbon is conducive to the clean utilization and high value-added application of coal resources. Coal liquefaction asphalt-based foamed carbon has a highly ordered graphite structure, high porosity, high specific surface area, low bulk density, and controllable structure. It is suitable for use in the fields of thermal insulation materials, catalyst carriers, electrode materials, etc.
[0004] In the prior art, the raw materials for the preparation of coal-based foamed carbon are mostly coal and coal tar pitch, and the research on the high value-added application of coal liquefied pitch is mainly carbon fiber, needle coke, mesoporous carbon, etc. There are few related preparation studies of foamed carbon materials with three-dimensional network structure, and most of the technical solutions are relatively cumbersome, making it difficult to achieve continuous and industrial production. In addition, the high polyester foam used in the soft template method in the prior art solution usually has a closed-cell diaphragm, and directly using it as a template will affect the impregnation effect in the raw material slurry and the microstructure and porosity of the obtained foamed carbon material. Summary of the invention
[0005] The present application provides a method for preparing coal liquefaction pitch-based foamed carbon, aiming to solve the problems of complex preparation process, small specific surface area and low porosity of coal-based foamed carbon in the prior art.
[0006] The present application provides a method for preparing coal liquefaction pitch-based foamed carbon, comprising the following steps:
[0007] (1) contacting the template with an alkali solution for hydrolysis treatment to obtain a pretreated template;
[0008] (2) contacting the pretreated template with an asphalt slurry to obtain a foamed carbon precursor;
[0009] (3) The carbon foam precursor is carbonized and activated to obtain coal liquefaction pitch-based carbon foam.
[0010] Since the template (polyurethane foam) has closed-cell, unfoamed membranes, using it directly as a template will affect the impregnation effect in the raw material slurry and the microstructure and porosity of the obtained foam carbon material. Hydrolyzing it with alkali solution can remove part of the membrane, which helps to improve the impregnation ability of the template, make the pore size of the prepared foam carbon more uniform, and have a higher open porosity and carbon yield.
[0011] The preparation method described in the present application uses coal liquefaction pitch as raw material to prepare foamed carbon, thereby improving the resource conversion and utilization efficiency in the direct coal liquefaction process and realizing high value-added utilization of coal resources.
[0012] The foamed carbon obtained by the preparation method described in the present application has the advantages of uniform pores, high specific surface area, high open porosity and high strength. It has a wide range of application scenarios, low production cost and simple process, and is suitable for industrial production.
[0013] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, in step (1), the template includes polyurethane foam and / or melamine foam.
[0014] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the alkali solution includes an aqueous sodium hydroxide solution and / or an aqueous potassium hydroxide solution; preferably, the alkali solution is an aqueous potassium hydroxide solution; more preferably, the mass concentration of the alkali solution is 10%-15%.
[0015] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, after the template is contacted with the alkali solution, the template is rinsed with deionized water and then dried to obtain a pretreated template.
[0016] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the hydrolysis temperature is 40-60° C., and the hydrolysis time is 40-70 min.
[0017] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the drying temperature is 80-120° C., and the drying time is 40-70 min.
[0018] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, in step (2), the asphalt slurry includes coal liquefaction pitch and a solvent.
[0019] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the mass ratio of the coal liquefaction pitch to the solvent is 1:(2-5).
[0020] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the solvent includes one or more of tetrahydrofuran, p-xylene and n-hexane.
[0021] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, in step (2), the contact time is 5-30 minutes.
[0022] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the preparation method further comprises pre-oxidation treatment of the foamed carbon precursor before the carbonization activation treatment.
[0023] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the foamed carbon precursor is subjected to a pre-oxidation treatment at 300-400° C. for 0.5-3 h.
[0024] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the foamed carbon precursor is placed in a carbonization furnace in an air atmosphere and heated to 300-400°C at a heating rate of 0.5-5°C / min, and kept warm for 0.5-3h for pre-oxidation treatment; more preferably, air is introduced into the carbonization furnace during the pre-oxidation treatment, and the air introduction rate is 1-50ml / min.
[0025] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the carbonization temperature is 500-900° C., and the carbonization time is 0.5-3 h.
[0026] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the carbonization is carried out under an inert atmosphere, and more preferably, the inert atmosphere includes one or more of a nitrogen atmosphere, an argon atmosphere, and a helium atmosphere.
[0027] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the carbonization is to place the foamed carbon precursor in a carbonization furnace with an inert atmosphere and raise the temperature to 500-900°C at a heating rate of 0.5-5°C / min, and keep it warm for 0.5-3h to perform carbonization treatment.
[0028] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the activation temperature is 600-900° C., and the activation time is 0.5-3 h.
[0029] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the activation is to raise the temperature of the carbonized foamed carbon precursor to 600-900°C at a heating rate of 0.5-5°C / min, while introducing water vapor for activation treatment.
[0030] According to some embodiments of the method for preparing coal liquefaction pitch-based foamed carbon described in the present application, the rate of introducing water vapor is 5-15 ml / h. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a SEM image of the pretreated polyurethane foam described in Example 1 of the present application;
[0032] Figure 2 This is a SEM image of the pretreated polyurethane foam described in Example 2 of the present application;
[0033] Figure 3 This is a SEM image of the pretreated polyurethane foam described in Example 3 of the present application;
[0034] Figure 4 This is a SEM image of the pretreated polyurethane foam described in Example 4 of the present application;
[0035] Figure 5 This is a SEM image of the pretreated polyurethane foam described in Example 5 of the present application;
[0036] Figure 6 This is a SEM image of the pretreated polyurethane foam described in Example 6 of the present application;
[0037] Figure 7 This is a SEM image of the pretreated polyurethane foam described in Example 7 of the present application;
[0038] Figure 8 This is a SEM image of the pretreated polyurethane foam described in Example 8 of the present application;
[0039] Fig. 9 This is a SEM image of the pretreated polyurethane foam described in Example 9 of the present application;
[0040] Fig.10 This is a SEM image of the pretreated polyurethane foam described in Example 10 of the present application;
[0041] Fig.11 This is a SEM image of the polyurethane foam described in Comparative Example 1 of the present application;
[0042] Fig.12 This is a SEM image of the coal liquefaction pitch-based foamed carbon described in Example 1 of the present application;
[0043] Fig.13 This is the SEM image of the coal liquefaction pitch-based foamed carbon described in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0044] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0045] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0046] The present invention provides a method for preparing coal liquefaction pitch-based foamed carbon, comprising the following steps:
[0047] (1) contacting the template with an alkali solution for hydrolysis treatment to obtain a pretreated template;
[0048] (2) contacting the pretreated template with an asphalt slurry to obtain a foamed carbon precursor;
[0049] (3) The carbon foam precursor is subjected to carbonization and activation treatment to obtain coal liquefaction pitch-based carbon foam.
[0050] Since the template (polyurethane foam) has closed-cell, unfoamed membranes, using it directly as a template will affect the impregnation effect in the raw material slurry and the microstructure and porosity of the obtained foam carbon material. Hydrolyzing it with alkali solution can remove part of the membrane, which helps to improve the impregnation ability of the template, make the pore size of the prepared foam carbon more uniform, and have a higher open porosity and carbon yield.
[0051] The preparation method described in the present application uses coal liquefaction pitch as raw material to prepare foamed carbon, thereby improving the resource conversion and utilization efficiency in the direct coal liquefaction process and realizing high value-added utilization of coal resources.
[0052] The foamed carbon obtained by the preparation method described in the present application has the advantages of uniform pores, high specific surface area, high open porosity and high strength. It has a wide range of application scenarios, low production cost and simple process, and is suitable for industrial production.
[0053] In some embodiments of the present application, in step (1), the template comprises polyurethane foam and / or melamine foam.
[0054] In some embodiments of the present application, the alkali solution includes an aqueous sodium hydroxide solution and / or an aqueous potassium hydroxide solution. The alkali solution can etch and form pores in the template (polyurethane foam) to solve the problem of small specific surface area of the foamed carbon obtained by the soft template method, and obtain a foamed carbon material with a higher specific surface area and porosity.
[0055] In some embodiments of the present application, the alkali solution is an aqueous solution of potassium hydroxide. Potassium hydroxide, as a commonly used activating agent, can play a good activation and pore-forming effect in the preparation process of porous carbon materials. The aqueous solution of potassium hydroxide is used for hydrolysis, and the potassium hydroxide remaining in the template can effectively improve the subsequent activation effect.
[0056] In some embodiments of the present application, the mass concentration of the alkali solution is 10%-15%. If the concentration of the alkali solution is too low, the treatment effect is poor and the diaphragm cannot be effectively removed; if the concentration of the alkali solution is too high, the skeleton structure of the template itself is destroyed and the foam loses its resilience. For example, 10%, 12%, 15%, etc.
[0057] In some embodiments of the present application, after the template is brought into contact with the alkaline solution, the template is rinsed with deionized water and then dried to obtain a pretreated template.
[0058] In some embodiments of the present application, the hydrolysis temperature is 40-60°C, for example, 40°C, 45°C, 50°C, 55°C, 58°C, 60°C, etc., and the hydrolysis time is 40-70min, for example, 40min, 45min, 50min, 55min, 58min, 60min, 65min, 70min, etc., and both the hydrolysis temperature and the hydrolysis time will affect the template pretreatment effect.
[0059] In some embodiments of the present application, the drying temperature is 80-120° C., and the drying time is 40-70 min.
[0060] In some embodiments of the present application, in step (2), the asphalt slurry includes coal liquefaction asphalt and a solvent.
[0061] In some embodiments of the present application, the mass ratio of the coal liquefaction pitch to the solvent is 1:(2-5), for example, 1:2, 1:3, 1:4, 1:5, etc.
[0062] In some embodiments of the present application, the solvent includes one or more of tetrahydrofuran, p-xylene and n-hexane.
[0063] In some embodiments of the present application, coal liquefaction asphalt and a solvent are mixed and ultrasonically treated for 10-30 minutes to obtain a stable and uniform asphalt slurry.
[0064] In some embodiments of the present application, in step (2), the contact time is 5-30 min, such as 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, etc. During the contact between the pretreated template and the asphalt slurry, the pretreated template is repeatedly squeezed to achieve the purpose of sufficient impregnation.
[0065] In some embodiments of the present application, the preparation method also includes pre-oxidation treatment of the foam carbon precursor before the carbonization activation treatment. The pre-oxidation treatment is to form a cross-linked structure of the polycyclic aromatic hydrocarbon molecules in the asphalt through a slight oxidation reaction, promote the transformation of the asphalt from thermoplastic to thermosetting, and cause solid-phase carbonization to occur, thereby avoiding the melting of the asphalt in the subsequent carbonization process.
[0066] In some embodiments of the present application, the foam carbon precursor is pre-oxidized at 300-400°C, such as 300°C, 320°C, 350°C, 400°C, etc., for 0.5-3h, such as 0.5h, 1h, 1.5h, 2h, 3h, etc.
[0067] In some embodiments of the present application, the foam carbon precursor is placed in a carbonization furnace in an air atmosphere and the temperature is increased to 300-400°C at a heating rate of 0.5-5°C / min, for example, 0.5°C / min, 1°C / min, 1.8°C / min, 2.3°C / min, 2.7°C / min, 3.2°C / min, 3.9°C / min, 4.3°C / min, and 5°C / min, and kept warm for 0.5-3h for pre-oxidation treatment.
[0068] In some embodiments of the present application, air is introduced into the carbonization furnace during the pre-oxidation treatment, and the air introduction rate is 1-50 ml / min, for example, 1 ml / min, 10 ml / min, 18 ml / min, 23 ml / min, 28 ml / min, 32 ml / min, 37 ml / min, 41 ml / min, 46 ml / min, 50 ml / min, etc.
[0069] In some embodiments of the present application, the carbonization temperature is 500-900° C., such as 500° C., 550° C., 600° C., 700° C., 800° C., 850° C., 900° C., etc. The carbonization time is 0.5-3 h, such as 0.5 h, 1 h, 2 h, 3 h, etc.
[0070] In some embodiments of the present application, the carbonization is performed under an inert atmosphere. More preferably, the inert atmosphere includes one or more of a nitrogen atmosphere, an argon atmosphere, and a helium atmosphere.
[0071] In some embodiments of the present application, the carbonization is to place the foam carbon precursor in a carbonization furnace with an inert atmosphere and raise the temperature to 500-900°C at a heating rate of 0.5-5°C / min, for example, 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.8°C / min, 4.3°C / min, 5°C / min, etc., and keep it warm for 0.5-3h for carbonization treatment.
[0072] In some embodiments of the present application, the activation temperature is 600-900°C, for example, 600°C, 650°C, 680°C, 720°C, 760°C, 810°C, 830°C, 900°C, etc., and the activation time is 0.5-3h, for example, 0.5h, 0.8h, 1.2h, 1.8h, 2.3h, 2.6h, 3h, etc.
[0073] In some embodiments of the present application, the activation is to heat the carbonized foamed carbon precursor to 600-900°C at a heating rate of 0.5-5°C / min, such as 0.5°C / min, 1.2°C / min, 1.8°C / min, 2.3°C / min, 3.2°C / min, 3.6°C / min, 4.3°C / min, 5°C / min, etc., and introduce water vapor for activation treatment. The introduction of water vapor can etch and form pores in the carbon precursor, thereby activating the carbon precursor.
[0074] In some embodiments of the present application, the rate of introducing water vapor is 5-15 ml / h, for example, 5 ml / h, 8 ml / h, 10 ml / h, 15 ml / h, 15 ml / h, etc.
[0075] The present application is further described below in conjunction with embodiments and drawings.
[0076] Example 1
[0077] A method for preparing coal liquefaction pitch-based foamed carbon comprises the following steps:
[0078] The template polyurethane foam was cut into rectangular blocks of 5×2×2 cm, placed in a 10% KOH solution, and hydrolyzed in a 60°C water bath for 50 min. After the hydrolysis was completed, the alkali solution was squeezed out, the polyurethane foam was rinsed with deionized water until it was neutral, and placed in a 105°C oven for 50 min to dry. The residual KOH can play a certain activation role in the subsequent experimental process.
[0079] 50 g of coal liquefaction asphalt crushed to a particle size of 100 mesh and 100 g of tetrahydrofuran were weighed and placed in a beaker, and then ultrasonicated for 30 min to obtain a uniformly distributed asphalt slurry. The pretreated polyurethane foam was completely immersed in the asphalt slurry for 20 min, and repeatedly squeezed and immersed during the period to achieve the purpose of full impregnation. After the impregnation was completed, the excess solvent was squeezed out and placed in a fume hood for 2 h to obtain a foamed carbon precursor.
[0080] The above-mentioned foamed carbon precursor was placed in a carbonization furnace, and in an air atmosphere (air was introduced into the carbonization furnace at a rate of 10 ml / min), the temperature was raised to 350°C at a rate of 1°C / min, and maintained for 1 hour to obtain a pre-oxidized precursor. The pre-oxidized precursor was heated to 350°C at a rate of 5°C / min in a carbonization furnace in a nitrogen atmosphere and maintained for 1 hour, and then heated to 700°C at a rate of 1°C / min and maintained for 1 hour for carbonization treatment. After the carbonization treatment, the temperature was raised to 800°C at a rate of 1°C / min and water vapor was introduced at a rate of 7.5 ml / h for 1 hour for activation treatment. After the activation, the temperature was naturally lowered to obtain coal liquefaction pitch-based foamed carbon.
[0081] Example 2
[0082] The method for preparing coal liquefaction pitch-based foamed carbon described in Example 2 is different from that in Example 1 in that the temperature and time of hydrolysis are different.
[0083] The specific operations are:
[0084] The template polyurethane foam was cut into rectangular blocks of 5×2×2 cm, placed in a 10% KOH solution, and hydrolyzed in a 65°C water bath for 65 min. After the hydrolysis was completed, the alkali solution was squeezed out, the polyurethane foam was rinsed with deionized water until it was neutral, and placed in a 105°C oven for 60 min to dry. The residual KOH can play a certain activation role in the subsequent experimental process.
[0085] 50 g of coal liquefaction asphalt crushed to a particle size of 100 mesh and 100 g of tetrahydrofuran were weighed and placed in a beaker, and then ultrasonicated for 30 min to obtain a uniformly distributed asphalt slurry. The pretreated polyurethane foam was completely immersed in the asphalt slurry for 20 min, and repeatedly squeezed and immersed during the period to achieve the purpose of full impregnation. After the impregnation was completed, the excess solvent was squeezed out and placed in a fume hood for 2 h to obtain a foamed carbon precursor.
[0086] The above-mentioned foamed carbon precursor was placed in a carbonization furnace, and in an air atmosphere (air was introduced into the carbonization furnace at a rate of 10 ml / min), the temperature was raised to 350°C at a rate of 1°C / min, and maintained for 1 hour to obtain a pre-oxidized precursor. The pre-oxidized precursor was heated to 350°C at a rate of 5°C / min in a carbonization furnace in a nitrogen atmosphere and maintained for 1 hour, and then heated to 700°C at a rate of 1°C / min and maintained for 1 hour for carbonization treatment. After the carbonization treatment, the temperature was raised to 800°C at a rate of 1°C / min and water vapor was introduced at a rate of 7.5 ml / h for 1 hour for activation treatment. After the activation, the temperature was naturally lowered to obtain coal liquefaction pitch-based foamed carbon.
[0087] Example 3
[0088] The preparation method of coal liquefaction pitch-based foamed carbon described in Example 3 is different from that in Example 1 only in that the mass concentration of potassium hydroxide is different.
[0089] The specific operations are:
[0090] The template polyurethane foam was cut into rectangular blocks of 5×2×2 cm, placed in a 15% KOH solution, and hydrolyzed in a 60°C water bath for 50 min. After the hydrolysis was completed, the alkali solution was squeezed out, the polyurethane foam was rinsed with deionized water until it was neutral, and placed in a 105°C oven for 60 min to dry. The residual KOH can play a certain activation role in the subsequent experimental process.
[0091] 50 g of coal liquefaction asphalt crushed to a particle size of 100 mesh and 100 g of tetrahydrofuran were weighed and placed in a beaker, and then ultrasonicated for 30 min to obtain a uniformly distributed asphalt slurry. The pretreated polyurethane foam was completely immersed in the asphalt slurry for 20 min, and repeatedly squeezed and immersed during the period to achieve the purpose of full impregnation. After the impregnation was completed, the excess solvent was squeezed out and placed in a fume hood for 2 h to obtain a foamed carbon precursor.
[0092] The above-mentioned foamed carbon precursor was placed in a carbonization furnace, and in an air atmosphere (air was introduced into the carbonization furnace at a rate of 10 ml / min), the temperature was raised to 350°C at a rate of 1°C / min, and maintained for 1 hour to obtain a pre-oxidized precursor. The pre-oxidized precursor was heated to 350°C at a rate of 5°C / min in a carbonization furnace in a nitrogen atmosphere and maintained for 1 hour, and then heated to 700°C at a rate of 1°C / min and maintained for 1 hour for carbonization treatment. After the carbonization treatment, the temperature was raised to 800°C at a rate of 1°C / min and water vapor was introduced at a rate of 7.5 ml / h for 1 hour for activation treatment. After the activation, the temperature was naturally lowered to obtain coal liquefaction pitch-based foamed carbon.
[0093] Example 4
[0094] The preparation method of coal liquefaction pitch-based foamed carbon described in Example 4 is different from that in Example 1 only in that the mass concentration of potassium hydroxide is different. The mass concentration of potassium hydroxide used in this example is 5%.
[0095] The template polyurethane foam was cut into rectangular blocks of 5×2×2 cm, placed in a 5% KOH solution, and hydrolyzed in a 60°C water bath for 50 min. After the hydrolysis was completed, the alkali solution was squeezed out, the polyurethane foam was rinsed with deionized water until it was neutral, and placed in a 105°C oven for 60 min to dry. The residual KOH can play a certain activation role in the subsequent experimental process.
[0096] Example 5
[0097] The preparation method of coal liquefaction pitch-based foamed carbon described in Example 5 is different from that in Example 1 only in that the mass concentration of potassium hydroxide is different. The mass concentration of potassium hydroxide used in this example is 20%.
[0098] The template polyurethane foam was cut into rectangular blocks of 5×2×2 cm, placed in a 20% KOH solution, and hydrolyzed in a 60°C water bath for 50 min. After the hydrolysis was completed, the alkali solution was squeezed out, the polyurethane foam was rinsed with deionized water until it was neutral, and placed in a 105°C oven for 60 min to dry. The residual KOH can play a certain activation role in the subsequent experimental process.
[0099] After the template polyurethane foam was hydrolyzed with 20% KOH and then immersed in asphalt slurry, the template polyurethane foam showed poor resilience, structural damage and collapse, and the next step of preparing foam carbon could not be carried out.
[0100] Example 6
[0101] The preparation method of coal liquefaction pitch-based foamed carbon described in Example 6 is different from that in Example 1 only in that the mass concentration of potassium hydroxide is different. The mass concentration of potassium hydroxide used in this example is 25%.
[0102] The template polyurethane foam was cut into rectangular blocks of 5×2×2 cm, placed in a 25% KOH solution, and hydrolyzed in a 60°C water bath for 50 min. After the hydrolysis was completed, the alkali solution was squeezed out, the polyurethane foam was rinsed with deionized water until it was neutral, and placed in a 105°C oven for 60 min to dry. The residual KOH can play a certain activation role in the subsequent experimental process.
[0103] After the template polyurethane foam is hydrolyzed with 25% KOH and then immersed in asphalt slurry, the template polyurethane foam loses its proper resilience, and structural damage and collapse occur, making it impossible to proceed to the next step of preparing foam carbon.
[0104] Example 7
[0105] The preparation method of coal liquefaction pitch-based foamed carbon described in Example 7 is different from that in Example 1 only in that the hydrolysis temperature is different, and the hydrolysis temperature in this example is 40°C.
[0106] The template polyurethane foam was cut into rectangular blocks of 5×2×2 cm, placed in a 10% KOH solution, and hydrolyzed in a 40°C water bath for 50 min. After the hydrolysis was completed, the alkali solution was squeezed out, the polyurethane foam was rinsed with deionized water until it was neutral, and placed in a 105°C oven for 60 min to dry. The residual KOH can play a certain activation role in the subsequent experimental process.
[0107] 50 g of coal liquefaction asphalt crushed to a particle size of 100 mesh and 100 g of tetrahydrofuran were weighed and placed in a beaker, and then ultrasonicated for 30 min to obtain a uniformly distributed asphalt slurry. The pretreated polyurethane foam was completely immersed in the asphalt slurry for 20 min, and repeatedly squeezed and immersed during the period to achieve the purpose of full impregnation. After the impregnation was completed, the excess solvent was squeezed out and placed in a fume hood for 2 h to obtain a foamed carbon precursor.
[0108] The above-mentioned foamed carbon precursor was placed in a carbonization furnace, and in an air atmosphere (air was introduced into the carbonization furnace at a rate of 10 ml / min), the temperature was raised to 350°C at a rate of 1°C / min, and maintained for 1 hour to obtain a pre-oxidized precursor. The pre-oxidized precursor was heated to 350°C at a rate of 5°C / min in a carbonization furnace in a nitrogen atmosphere and maintained for 1 hour, and then heated to 700°C at a rate of 1°C / min and maintained for 1 hour for carbonization treatment. After the carbonization treatment, the temperature was raised to 800°C at a rate of 1°C / min and water vapor was introduced at a rate of 7.5 ml / h for 1 hour for activation treatment. After the activation, the temperature was naturally lowered to obtain coal liquefaction pitch-based foamed carbon.
[0109] Example 8
[0110] The preparation method of coal liquefaction pitch-based foamed carbon described in Example 8 is different from that in Example 1 only in that the hydrolysis temperature is different, and the hydrolysis temperature in this example is 50°C.
[0111] The template polyurethane foam was cut into rectangular blocks of 5×2×2 cm, placed in a 10% KOH solution, and hydrolyzed in a 50°C water bath for 50 min. After the hydrolysis was completed, the alkali solution was squeezed out, the polyurethane foam was rinsed with deionized water until it was neutral, and placed in a 105°C oven for 60 min to dry. The residual KOH can play a certain activation role in the subsequent experimental process.
[0112] 50 g of coal liquefaction asphalt crushed to a particle size of 100 mesh and 100 g of tetrahydrofuran were weighed and placed in a beaker, and then ultrasonicated for 30 min to obtain a uniformly distributed asphalt slurry. The pretreated polyurethane foam was completely immersed in the asphalt slurry for 20 min, and repeatedly squeezed and immersed during the period to achieve the purpose of full impregnation. After the impregnation was completed, the excess solvent was squeezed out and placed in a fume hood for 2 h to obtain a foamed carbon precursor.
[0113] The above-mentioned foamed carbon precursor was placed in a carbonization furnace, and in an air atmosphere (air was introduced into the carbonization furnace at a rate of 10 ml / min), the temperature was raised to 350°C at a rate of 1°C / min, and maintained for 1 hour to obtain a pre-oxidized precursor. The pre-oxidized precursor was heated to 350°C at a rate of 5°C / min in a carbonization furnace in a nitrogen atmosphere and maintained for 1 hour, and then heated to 700°C at a rate of 1°C / min and maintained for 1 hour for carbonization treatment. After the carbonization treatment, the temperature was raised to 800°C at a rate of 1°C / min and water vapor was introduced at a rate of 7.5 ml / h for 1 hour. After the activation was completed, the temperature was naturally lowered to obtain coal liquefaction pitch-based foamed carbon.
[0114] Example 9
[0115] The preparation method of coal liquefaction pitch-based foamed carbon described in Example 9 is different from that in Example 1 only in that the hydrolysis temperature is different. The hydrolysis temperature in this example is 70°C.
[0116] The template polyurethane foam was cut into rectangular blocks of 5×2×2 cm, placed in a 10% KOH solution, and hydrolyzed in a 70°C water bath for 50 min. After the hydrolysis was completed, the alkali solution was squeezed out, the polyurethane foam was rinsed with deionized water until it was neutral, and placed in a 105°C oven for 60 min to dry. The residual KOH can play a certain activation role in the subsequent experimental process.
[0117] Since the hydrolysis temperature of the template polyurethane foam is too high, the toughness and resilience of the template are poor when immersed in asphalt slurry, resulting in structural damage and collapse, making it impossible to proceed to the next step.
[0118] Example 10
[0119] The preparation method of coal liquefaction pitch-based foamed carbon described in Example 10 is different from that in Example 1 only in that the alkali solution used in this example is an aqueous sodium hydroxide solution.
[0120] The template polyurethane foam was cut into rectangular blocks of 5×2×2 cm, placed in a 10% NaOH solution, and hydrolyzed in a 60°C water bath for 50 min. After the hydrolysis was completed, the alkali solution was squeezed out, the polyurethane foam was rinsed with deionized water until it was neutral, and placed in a 105°C oven for 60 min to dry.
[0121] 50 g of coal liquefaction asphalt crushed to a particle size of 100 mesh and 100 g of tetrahydrofuran were weighed and placed in a beaker, and then ultrasonicated for 30 min to obtain a uniformly distributed asphalt slurry. The pretreated polyurethane foam was completely immersed in the asphalt slurry for 20 min, and repeatedly squeezed and immersed during the period to achieve the purpose of full impregnation. After the impregnation was completed, the excess solvent was squeezed out and placed in a fume hood for 2 h to obtain a foamed carbon precursor.
[0122] The above-mentioned foamed carbon precursor was placed in a carbonization furnace, and in an air atmosphere (air was introduced into the carbonization furnace at a rate of 10 ml / min), the temperature was raised to 350°C at a rate of 1°C / min, and maintained for 1 hour to obtain a pre-oxidized precursor. The pre-oxidized precursor was heated to 350°C at a rate of 5°C / min in a carbonization furnace in a nitrogen atmosphere and maintained for 1 hour, and then heated to 700°C at a rate of 1°C / min and maintained for 1 hour for carbonization treatment. After the carbonization treatment, the temperature was raised to 800°C at a rate of 1°C / min and water vapor was introduced at a rate of 7.5 ml / h for 1 hour for activation treatment. After the activation, the temperature was naturally lowered to obtain coal liquefaction pitch-based foamed carbon.
[0123] Comparative Example 1
[0124] The preparation method of coal liquefaction pitch-based foamed carbon described in Comparative Example 1 is different from that in Example 1 only in that: in Comparative Example 1, the template polyurethane foam is not contacted with an alkali solution for hydrolysis treatment.
[0125] The specific operations are:
[0126] 50g of coal liquefaction asphalt crushed to a particle size of 100 mesh and 100g of tetrahydrofuran were weighed and placed in a beaker, and then ultrasonicated for 30 minutes to obtain a uniformly distributed asphalt slurry. A 5×2×2cm polyurethane foam template was completely immersed in the asphalt slurry for 20 minutes, and repeatedly squeezed and immersed during the period to achieve the purpose of full impregnation. After the impregnation was completed, the excess solvent was squeezed out and placed in a fume hood for 2 hours to obtain a foam carbon precursor.
[0127] The above-mentioned foamed carbon precursor was placed in a carbonization furnace, and in an air atmosphere (air was introduced into the carbonization furnace at a rate of 10 ml / min), the temperature was raised to 350°C at a rate of 1°C / min, and maintained for 1 hour to obtain a pre-oxidized precursor. The pre-oxidized precursor was heated to 350°C at a rate of 5°C / min in a carbonization furnace in a nitrogen atmosphere and maintained for 1 hour, and then heated to 700°C at a rate of 1°C / min and maintained for 1 hour for carbonization treatment. After the carbonization treatment, the temperature was raised to 800°C at a rate of 1°C / min and water vapor was introduced at a rate of 7.5 ml / h for 1 hour for activation treatment. After the activation, the temperature was naturally lowered to obtain coal liquefaction pitch-based foamed carbon.
[0128] Study on the physical properties of coal liquefaction pitch-based foamed carbon prepared in Examples 1-10 and Comparative Example 1 of the present application:
[0129] The results are shown in Table 1:
[0130] Table 1
[0131]
[0132]
[0133] Note: The method for determining the bulk density of the embodiments of the present application is: testing according to JB / T8133.14-2013 "Test methods for physical and chemical properties of electric carbon products Part 14: Bulk density";
[0134] The porosity of the present invention is determined by using a MicroActiveAutoPore V 9600 fully automatic mercury intrusion instrument.
[0135] The test method of the specific surface area in the embodiment of the present application is: using Micromeritics' 3Flex all-functional multi-purpose adsorption meter to characterize the pore structure characteristics of the material, and calculating the specific surface area of the material according to the BET theory.
[0136] Since the alkali concentration used in Example 4 during hydrolysis was too low, the effect of removing the diaphragm was limited, resulting in residual diaphragm in the template, and no further operation was performed to prepare foamed carbon; since the alkali concentration in Example 5 and Example 6 was too high during hydrolysis, the structure of the template polyurethane foam was destroyed, and no further operation was performed to prepare foamed carbon; since the hydrolysis temperature in Example 9 was too high, the structure of the template polyurethane foam was destroyed, and the next step of operation could not be performed.
[0137] It can be seen from Table 1 that the preparation method of coal liquefaction pitch-based foam carbon described in the present application improves the physical properties of the obtained foam carbon by contacting the template polyurethane foam with alkali solution for hydrolysis treatment. The porosity of the foam carbon is increased from 81.90% to 93.95% without hydrolysis treatment, and the specific surface area is increased from 230.24m 2 / g increased to 765.55m 2 / g, the bulk density is 0.053g / cm 3 Down to 0.035g / cm 3 ;
[0138] After the template polyurethane foam is hydrolyzed, the mass increases by about 10-25% due to the residual potassium hydroxide. From the data of Example 1 and Example 10 in Table 1, it can be seen that the specific surface areas of the template polyurethane foam using 10% KOH and 10% NaOH as the alkali solution for hydrolysis are 515.73m 2 / g and 308.23m2 / g, the activation effect of KOH effectively increases the specific surface area of the product.
[0139] The SEM images of the polyurethane foams rinsed to neutrality after hydrolysis described in Examples 1-10 of the present application are shown in FIG. Figure 1-10 As shown; the SEM image of the polyurethane foam described in Comparative Example 1 of the present application is as shown Fig.11 As shown; the SEM image of the coal liquefaction pitch-based foam carbon described in Example 1 of the present application is as shown Fig.12 As shown; the SEM image of the coal liquefaction pitch-based foam carbon described in Comparative Example 1 of the present application is as shown Fig.13 shown.
[0140] from Figure 1 and Fig.11 It can be seen that the template polyurethane foam can be effectively removed from the unfoamed diaphragm in the PU foam cells by hydrolysis with an alkaline solution.
[0141] from Figure 1 , Figure 4 , Figure 5 , Figure 6 , Fig. 9 It can be seen that: when the template polyurethane foam is hydrolyzed, if the alkali concentration is too low, the effect of removing the diaphragm is limited, resulting in residual diaphragm in the template; if the alkali concentration is too high during hydrolysis, the color of the template will be significantly darker, the degree of skeleton corrosion will be aggravated, and the foam will lose its resilience; similarly, if the hydrolysis temperature is too high, the structure of the template polyurethane foam will be destroyed.
[0142] from Fig.12 and Fig.13 It can be seen that the foam carbon prepared from the template polyurethane foam without hydrolysis treatment has an obvious closed-cell structure.
[0143] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A method for preparing coal liquefaction pitch-based foamed carbon, characterized in that: The following steps are involved: (1) contacting the template with an alkali solution for hydrolysis treatment to obtain a pretreated template; (2) contacting the pretreated template with an asphalt slurry to obtain a foamed carbon precursor; (3) The carbon foam precursor is carbonized and activated to obtain coal liquefaction pitch-based carbon foam.
2. The method for preparing coal liquefaction pitch-based foamed carbon according to claim 1, characterized in that: In step (1), the template comprises polyurethane foam and / or melamine foam; And / or, the alkali solution includes sodium hydroxide aqueous solution and / or potassium hydroxide aqueous solution; preferably, the alkali solution is potassium hydroxide aqueous solution; more preferably, the mass concentration of the alkali solution is 10%-15%; And / or, after the template agent is brought into contact with the alkaline solution, the template agent is rinsed with deionized water and then dried to obtain a pretreated template.
3. The method for preparing coal liquefaction pitch-based foamed carbon according to claim 2, characterized in that: The hydrolysis temperature is 40-60°C, and the hydrolysis time is 40-70min; And / or, the drying temperature is 80-120° C., and the drying time is 40-70 min.
4. The method for preparing coal liquefaction pitch-based foamed carbon according to claim 1, characterized in that: In step (2), the asphalt slurry comprises coal liquefaction asphalt and a solvent; Preferably, the mass ratio of the coal liquefaction pitch to the solvent is 1:(2-5); Preferably, the solvent comprises one or more of tetrahydrofuran, p-xylene and n-hexane; And / or, in step (2), the contact time is 5-30 min.
5. The method for preparing coal liquefaction pitch-based foamed carbon according to claim 1, characterized in that: The preparation method further comprises pre-oxidizing the foam carbon precursor before the carbonization activation treatment; Preferably, the carbon foam precursor is pre-oxidized at 300-400° C. for 0.5-3 h. Preferably, the foamed carbon precursor is placed in a carbonization furnace in an air atmosphere and heated to 300-400°C at a heating rate of 0.5-5°C / min, and kept warm for 0.5-3h for pre-oxidation treatment; more preferably, air is introduced into the carbonization furnace during the pre-oxidation treatment, and the air introduction rate is 1-50ml / min.
6. The method for preparing coal liquefaction pitch-based foamed carbon according to claim 1, characterized in that: The carbonization temperature is 500-900°C, and the carbonization time is 0.5-3h; Preferably, the carbonization is performed under an inert atmosphere, and more preferably, the inert atmosphere includes one or more of a nitrogen atmosphere, an argon atmosphere, and a helium atmosphere.
7. The method for preparing coal liquefaction pitch-based foamed carbon according to claim 1, characterized in that: The carbonization is to place the foamed carbon precursor in a carbonization furnace with an inert atmosphere, raise the temperature to 500-900° C. at a heating rate of 0.5-5° C. / min, and keep the temperature for 0.5-3 hours to perform carbonization treatment.
8. The method for preparing coal liquefaction pitch-based foamed carbon according to claim 1, characterized in that: The activation temperature is 600-900° C., and the activation time is 0.5-3 h.
9. The method for preparing coal liquefaction pitch-based foamed carbon according to claim 1, characterized in that: The activation is to heat the carbonized foam carbon precursor to 600-900° C. at a heating rate of 0.5-5° C. / min, while introducing water vapor to perform activation treatment.
10. The method for preparing coal liquefaction pitch-based foamed carbon according to claim 9, characterized in that: The rate of introducing water vapor is 5-15 ml / h.
Citation Information
Cited By
Preparation method and application of nickel monatomic sulfur-nitrogen co-doped foam carbon monolithic catalyst
CN120231067A
Waste paper-based carbon foam capable of being used for interface light evaporation seawater desalination and preparation method and application of waste paper-based carbon foam
CN121449038A